Opaque cell-specific proteome of Candida albicans ATCC 10231 - Abdulghani, Mazen; Telang, Saraswati; Desai, Manisha; Kadam, Shivdas; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra; Maurya, Radheshyam; Zore, Gajanan (Medical Mycology, 2023)
Candida albicans, a polymorphic opportunistic pathogen of humans, can exist in different morphological forms like yeast, hyphae, pseudohyphae, chlamydospores, and white and opaque cells. Proteomic analysis of opaque form of C. albicans ATCC 10231 is carried out in the present study using microflow liquid chromatography-tandem mass spectrometry and validated using expression analysis of selected genes using reverse transcription quantitative real-time PCR and mitochondrial membrane potential assay. This is the first report identifying opaque cell-specific proteins of C. albicans. A total of 188 proteins were significantly modulated under opaque form compared to white cells, of which 110 were upregulated, and 78 were downregulated. It was observed that oxidative phosphorylation (OxPhos) and oxidative stress are enhanced in C. albicans cells growing under opaque form as proteins involved in OxPhos (Atp1, Atp3, Atp16, Atp7, Cox6, Nuc2, Qcr7, and Sdh12) and oxidative stress response (Gcs1, Gtt11, Gpx2, Sod1, Ccp1, and Lys7) were significantly upregulated. The maximum upregulation of 23.16- and 13.93-fold is observed in the cases of Ccp1 and Nuc2, respectively. The downregulation of proteins, namely Als1, Csh1, Sap9, and Rho1, determining cell surface chemistry indicates modulation in cell wall integrity and reduced adhesion of opaque cells compared to white cells. This study is significant as it is the first draft of the proteomic profile of opaque cells that suggests enhanced OxPhos, oxidative stress, and modulation in cell surface chemistry indicating reduced adhesion and cell wall integrity, which could be associated with reduced virulence in opaque form. However, a deeper investigation is needed to explore it further. Lay Summary Opaque form is one of the least studied morphological forms of Candida albicans. To the best of our knowledge, this is the first report providing opaque cell-specific proteome. It suggests enhanced oxidative phosphorylation, oxidative stress, and modulation in cell surface chemistry, which could be associated with reduced virulence in opaque form.
Keywords: albicans; C; LC-MS; MS; opaque; Oxidative stress; OxPhos; protein